An Experimental Research of Using Heroes Mobile Legends Bang-Bang (MLBB) on Writing Legend Stories - Vivi Aulia; Dewi Nopita; Hanifah (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This research aimed to know whether is there any effect or not of using heroes Mobile Legends Bang-Bang (MLBB) on writing a legend story at tenth grade students of SMA Negeri 5 Batam in the academic year 2022/2023. The researcher selected X Science 1 as a sample and totaled 44 students as the research object. The researcher used a quantitative method to find out the answer to the research problem. The design of this research used an experimental design with a one-group pre-test and post-test control design and gave four times for the treatments. This research used a writing test as the Instrument to collect the data. Based on the data analysis result, showed the null hypothesis (H0) and alternative hypothesis 2 (H2) were rejected and alternative hypothesis 1 (H1) was accepted. It could be seen from data calculated using paired sample t-test formula that the significance was 0.728 and distributed normally because 0.728 > 0.005 while the Sig. 2 tailed was 0.000 which means that there was the effect of using heroes Mobile Legends Bang-Bang (MLBB) on writing a legend story at tenth grade students of SMA Negeri 5 Batam because the Sig. 2 tailed 0.000 < 0.005. Based on the findings, researcher suggested to the teacher to use heroes Mobile Legends Bang-Bang (MLBB) for teaching writing a legend story because this material gave effect on students’ writing skills.